Reported Signs, Symptoms, and Diagnostic Tests Before Cardiotoxicity Among Women With Breast Cancer: A Pilot Study. Issue 2 (March 2022) - Attin, Mina; Reifenstein, Karen; Mehta, Sakshi; Arcoleo, Kimberly; Lin, C.D.; Storozynsky, Eugene
Abstract : Background: Cardiotoxicity after cancer treatment is a potentially preventable life-threatening complication among women with breast cancer. There is no algorithm to identify women with breast cancer at risk of cardiotoxicity. Objectives: We quantified signs and symptoms as well as selected laboratory values among women with breast cancer who developed cardiotoxicity. Methods: The clinical characteristics (n = 15) were collected from electronic health records. Spearman correlation coefficients and a nonparametric statistical test were used to analyze data. Results: Significant statistical differences were detected in the laboratory values comparing the first and second half of 6 months before cardiotoxicity including alanine aminotransferase (U/L) (30.67 ± 26.27 and 42.31 ± 35.65, respectively; P = .03, Cohen's d = 0.37). A negative correlation was found between estimated glomerular filtration rate and new onset of more than 1 sign or symptom (Spearman's ρ = −0.5, P = .06). Conclusions: Investigating clinical characteristics before cardiotoxicity may determine the mechanism(s) and identify high-risk patients.